2011
DOI: 10.1007/s12975-011-0110-4
|View full text |Cite
|
Sign up to set email alerts
|

Defining an Acidosis-Based Ischemic Penumbra from pH-Weighted MRI

Abstract: It has been proposed that the spatial mismatch between deficits on perfusion-weighted imaging (PWI) and diffusion-weighted imaging (DWI) in MRI can be used to decide regarding thrombolytic treatment in acute stroke. However, uncertainty remains about the meaning and reversibility of the perfusion deficit and even part of the diffusion deficit. Thus, there remains a need for continued development of imaging technology that can better define a potentially salvageable ischemic area at risk of infarction. Amide pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
75
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(80 citation statements)
references
References 55 publications
5
75
0
Order By: Relevance
“…However, when impaired perfusion is significant enough to affect metabolism, a systemic intracellular acidosis ensues propagating out from a central infarct core, sparing regions of oligemia that have not resulted in anaerobic metabolism. Our observations show that pH deficits are smaller than perfusion deficits and equal to or larger than diffusion deficits, in line with previous animal studies (26, 27, 48). The pH deficit may reflect the area of final infarction expected without reperfusion and thus, the acidosis-based penumbra.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, when impaired perfusion is significant enough to affect metabolism, a systemic intracellular acidosis ensues propagating out from a central infarct core, sparing regions of oligemia that have not resulted in anaerobic metabolism. Our observations show that pH deficits are smaller than perfusion deficits and equal to or larger than diffusion deficits, in line with previous animal studies (26, 27, 48). The pH deficit may reflect the area of final infarction expected without reperfusion and thus, the acidosis-based penumbra.…”
Section: Discussionsupporting
confidence: 93%
“…APT studies interpreted using the EMR approach showed less contaminated APT-MRI signals, and concomitant enhanced APT-MRI sensitivity to pH, allowing reliable delineation of an ischemic acidosis penumbra. The spatial distributions of the diffusion deficits, pH-diffusion mismatches, and perfusion-pH mismatches suggest that hypoperfused acidic ischemic lesions without an ADC abnormality identified the ischemic acidosis penumbra, while the hypoperfused neural area classified benign oligemia in line with the hypotheses previously suggested (26, 27, 48). Interestingly, the intracerebral hemorrhage and ischemic stroke lesions showed opposite APT signal features which are hyperintensity and hypointensity compared with the contralateral normal brain tissue, respectively.…”
Section: Discussionsupporting
confidence: 83%
“…T 1 , T 2 , and diffusion) have been applied to diagnose ischemic stroke (2528). Amide proton transfer (APT), a variation of MT or CEST technique, which originates from backbone amide protons associated with endogenous mobile, cytosolic proteins and peptides in biological tissue has been used previously to distinguish benign oligemia from the ischemic penumbra (20,29). It was reported that these MRI contrasts reflect different physiological or metabolic changes during stroke (15,3032).…”
Section: Introductionmentioning
confidence: 99%
“…The use of APT imaging has been suggested to help stroke depiction by subdividing the perfusion-diffusion mismatched region into regions with and without tissue acidosis (1,2). Diffusion restricted regions often represent an ischemic core, but they can sometimes recover (14), and perfusion-weighted imaging also includes regions with benign oligemia.…”
Section: Discussionmentioning
confidence: 99%